2016
DOI: 10.1007/s13277-016-5124-9
|View full text |Cite
|
Sign up to set email alerts
|

Low absolute CD4+ T cell counts in peripheral blood are associated with inferior survival in follicular lymphoma

Abstract: Host immunity and tumor microenvironment significantly influence follicular lymphoma (FL) outcomes. Lymphopenia has been identified as a negative prognostic factor for FL. However, there is limited data regarding prognostic value of peripheral blood T lymphocyte subsets, especially absolute CD4 T cell counts (ACD4C) in FL. We studied 127 consecutive FL patients to investigate whether peripheral blood ACD4C or absolute monocytes (AMC) at diagnosis had an impact on FL prognosis. In our cohort, both low ACD4C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies showed that compared to normal people, cancer patients had decreased CD3+, CD4+ count, but elevated CD8+ count (11,12,(25)(26)(27). In addition, stage IV breast cancer and the Her-2/VEGF-positive breast cancer patients have worsened immune function (12) and poor survival prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that compared to normal people, cancer patients had decreased CD3+, CD4+ count, but elevated CD8+ count (11,12,(25)(26)(27). In addition, stage IV breast cancer and the Her-2/VEGF-positive breast cancer patients have worsened immune function (12) and poor survival prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment has been shown to be a prognostic marker in certain types of lymphomas [17-20]. Regarding host immunity, several studies correlating circulating immune populations of peripheral blood cells with outcome in B-cell lymphoma have been reported [13,14,21]. Patients with decreased numbers of CD4 + T cells showed inferior OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 127 FL patients revealed that low ACD4Cs were statistically significantly associated with a worse PFS and shorter OS. Evaluation of peripheral blood ACD4Cs could be a useful indicator of outcome in previously untreated FL patients [13]. Similarly, Zhang et al [14] reported that both low ACD4Cs and CD4/CD8 ratios were associated with unfavorable OS by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation